Values explication in the Russian media discourse: columnist and adressat - Kaminskaya, Tatiana (Przegląd Wschodnioeuropejski, 2018)
In Russian society it is not accepted to speak openly about their values: they serve as a motive for political preferences or social actions. However, in the media discourse they are explicated in the publications of columnists and sometimes even brighter in the reaction of addressees to their texts (in the comments). In fact, the columnist (a relatively new phenomenon for Russian journalism) in his essays/ author’s columns discusses the value of things, and commentators express in response their own value judgments. Semantic reconstruction for example, in public-political newspaper “Vedomosti” and “Novaya gazeta” helps to isolate the core values of a modern Russian society.